(untitled) (Itinera, 2015)
The essay proposes an interpretation of the myth of the cave as a passage from a digital ontology (that of the cave) to a non-digital ontology (outside the cave). This passage implies a reconsideration of Parmenidean and Pythagorean ontology, for which the discovery of incommensurable magnitudes is central. In particular, it allows an exteriority (as difference, negativity, dynamis, and so on) to a given system to be conceptualized, in which the possibility of an exit and then of freedom lies.